Effect of Processing Parameters on Proteolysis during ripening in Cheddar cheese - Hossain, Shamim; Khetra, Yogesh; Ganguly, Sangita; Sabikhi, Latha (Indian Journal of Dairy Science, 2019)
Proteolysis in Cheddar cheese, caused by various proteolytic enzymes present in cheese system, results production of the smaller peptides. The current research was conducted to study the effect of heating temperature (72ËšC, 75ËšC, 78ËšC/15 second) and level of salting (1%, 1.5%, 2%) on proteolysis in Cheddar cheese during ripening. The extent of proteolysis was measured quantitatively by soluble protein content and qualitatively by the urea-PAGE throughout the four months of ripening. Soluble protein content also reflects the extent of ripening of Cheddar cheese. During ripening an increase was found in the soluble protein content. The urea-PAGE had shown the degradation of Î²-casein and Î±S1-casein to smaller fraction of Î³-caseins and proteose-peptones. The highest soluble protein content (21.74 %w/w) was found in sample 75ËšC/15 second heat treatment and 2% salt content at the 4th month of ripening. The effect of heat treatment and level of salting was not reflected in urea-PAGE, but it had shown the clear picture of degradation of native caseins to peptides during ripening.Â Â Â